2000
DOI: 10.1111/j.1741-3737.2000.00430.x
|View full text |Cite
|
Sign up to set email alerts
|

Subsequent Fertility Among Teen Mothers: Longitudinal Analyses of Recent National Data

Abstract: A sample of high school age mothers was followed from 1988 to 1994 in order to examine factors associated with having a second teen birth or a closely spaced second birth. The study incorporates a life-course perspective. Factors associated with postponing a subsequent birth include characteristics measured prior to the first birth, at the time of the first birth, and after the first birth. Analyses suggest that a combination of young teen mothers staying in school, living at home with their parents, and (amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 29 publications
(45 reference statements)
3
46
0
1
Order By: Relevance
“…Similar to other research using a different database (Manlove et al, 2000), we found that living with parents was associated with lower odds of a nonmarital subsequent birth. This finding suggests that policies which dictate that young mothers must live with an adult in order to receive welfare benefits may have a positive effect on reducing higher-order births among teens.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to other research using a different database (Manlove et al, 2000), we found that living with parents was associated with lower odds of a nonmarital subsequent birth. This finding suggests that policies which dictate that young mothers must live with an adult in order to receive welfare benefits may have a positive effect on reducing higher-order births among teens.…”
Section: Discussionsupporting
confidence: 90%
“…We expect a curvilinear relationship between age of youngest child and subsequent birth, with a lower likelihood of an additional birth at the ends of the age distribution. Women living at home with a parent are typically less likely to have an additional birth (Manlove et al, 2000).…”
Section: Welfare Reform Effects On Employment and Incomementioning
confidence: 99%
“…Greater spacing between pregnancies can lead to healthier pregnancy outcomes or to a decision not to become Downloaded by [University of Nebraska, Lincoln] at 13:22 13 April 2015 pregnant again until after graduation. Moreover, as the literature suggests, a second or a third closely spaced child makes it even more difficult for the teen mothers to access educational and occupational opportunities (Manlove, Mariner, & Papillo, 2000). The fact that there was essentially no difference in the delay in the timing of repeat pregnancies between intervention and comparison program parenting teens could be due to small sample sizes, especially among the comparison group.…”
Section: Discussionmentioning
confidence: 96%
“…With regard to maternal life course, subsequent births to teen mothers, especially closely spaced ones, make it difficult for the mothers to move out of poverty (Harris 1996;Horwitz et al 1991;Stewart and Dooley 1999). In addition, adolescent mothers who have closely spaced births are more likely to have lower levels of educational attainment, drop out of high school, and depend upon public assistance (Dailard 2000;Furstenberg et al 1987;Manlove et al 2000). These findings, along with research on the negative outcomes of early child rearing in general, support an emphasis on the prevention of TRBs as a key public health policy initiative.…”
Section: The Effects Of Teen Repeat Births On Child Health and Develomentioning
confidence: 96%